Biphasic expression of thyroid hormone receptor TRβ1 in mammalian retina and anterior ocular tissues - Ng, Lily; Liu, Hong; Liu, Ye; Forrest, Douglas (Frontiers in Endocrinology, 2023)
The retina is increasingly recognized as a target of thyroid hormone. We previously reported critical functions for thyroid hormone receptor TRβ2, encoded by Thrb, in cones, the photoreceptors that mediate color vision. TRβ1, another Thrb receptor isoform, is widely expressed in other tissues but little studied in the retina. Here, we investigate these N-terminal isoforms by RNA-sequencing analysis and reveal a striking biphasic profile for TRβ1 in mouse and human retina. In contrast to the early TRβ2 peak, TRβ1 peaks later during retinal maturation or later differentiation of human retinal organoids. This switch in receptor expression profiles was confirmed using lacZ reporter mice. TRβ1 localized in cones, amacrine cells and ganglion cells in contrast to the restricted expression of TRβ2 in cones. Intriguingly, TRβ1 was also detected in the retinal pigmented epithelium and in anterior structures in the ciliary margin zone, ciliary body and iris, suggesting novel functions in non-retinal eye tissues. Although TRβ1 was detected in cones, TRβ1-knockout mice displayed only minor changes in opsin photopigment expression and normal electroretinogram responses. Our results suggest that strikingly different temporal and cell-specific controls over TRβ1 and TRβ2 expression may underlie thyroid hormone actions in a range of ocular cell types. The TRβ1 expression pattern suggests novel functions in retinal and non-neural ocular tissues.